(untitled) (Health Renaissance, 2012)
Patient safety should be at the core of health care delivery. The main motto of the health care industry is to help the people in fighting illness using safe products. We have seen news headlines about recalls because of faulty products that result in harm to the user; these have occurred not only in the pharmaceutical industry but also in the device industry. Harm may be accrued from mislabeling, defective parts and/or defective ingredients. The question is how to remedy the situation once the product has been in wide circulation perhaps not just in one country but across the globe. Many times we have experienced hardships due to the recall of consumer goods such as cars, refrigerators, toys, etc. Recalls due to safety concerns should be implemented immediately, otherwise potential harm from product use will result in the injury or death of the users. Electronic health records (EHR) will help immediately track down the patients using defective products (in this case, medical devices or drugs). It will thus help save lives by early notification to the users of these potentially harmful products. DOI: http://dx.doi.org/10.3126/hren.v10i2.6581 Health Renaissance 2012; Vol 10 (No.2); 132-133